Forest Health in the Southern Cone of America: State of the Art and Perspectives on Regional Efforts - Villacide, José M.; Gomez, Demian F.; Perez, Carlos A.; Corley, Juan C.; Ahumada, Rodrigo; Rodrigues Barbosa, Leonardo; Furtado, Edson Luiz [UNESP]; González, Andrés; Ramirez, Nazaret; Balmelli, Gustavo; Dias de Souza, Caroline; Martínez, Gonzalo (MDPI, 2023)
The plantation and natural forests of South America have been highly impacted by native and exotic pests in recent decades. The interaction of emerging invasive pests, climate change, and timber markets will define the region’s forests, with significant but uncertain ecological changes and economic losses expected. The Southern Cone Forest Health Group (SCFHG), a joint ad hoc initiative run by forest health professionals from Argentina, Brazil, Chile, and Uruguay, aims to strengthen relationships between the forestry industry, stakeholders, academia, and government agencies across the region. Here, we highlight regional strengths, weaknesses, threats, and opportunities to address forest health issues in the region. A regional approach with a strong communication network is relevant for future actions. In the current global scenario of invasive species and climate change, the implementation of practices that incorporate the resilience of forest ecosystems and sustainable management needs to be prioritized in forest policy across the region. Understanding that pests and pathogens do not recognize borders, we call on governments and organizations to support joint actions with agreements and adequate resources to enhance our regional capabilities.
Keywords: forest entomology; forest pathology; invasive alien species; plantation forestry; regional initiatives